Multi‐year carbon budget of a mature commercial short rotation coppice willow plantation. Issue 7 (5th March 2019) - Morrison, Ross; Rowe, Rebecca L; Cooper, Hollie M.; McNamara, Niall P.
Abstract: Energy derived from second generation perennial energy crops is projected to play an increasingly important role in the decarbonization of the energy sector. Such energy crops are expected to deliver net greenhouse gas emissions reductions through fossil fuel displacement and have potential for increasing soil carbon (C) storage. Despite this, few empirical studies have quantified the ecosystem‐level C balance of energy crops and the evidence base to inform energy policy remains limited. Here, the temporal dynamics and magnitude of net ecosystem carbon dioxide (CO2 ) exchange (NEE) were quantified at a mature short rotation coppice (SRC) willow plantation in Lincolnshire, United Kingdom, under commercial growing conditions. Eddy covariance flux observations of NEE were performed over a four‐year production cycle and combined with biomass yield data to estimate the net ecosystem carbon balance (NECB) of the SRC. The magnitude of annual NEE ranged from −147 ± 70 to −502 ± 84 g CO2 ‐C m −2  year −1 with the magnitude of annual CO2 capture increasing over the production cycle. Defoliation during an unexpected outbreak of willow leaf beetle impacted gross ecosystem production, ecosystem respiration, and net ecosystem exchange during the second growth season. The NECB was −87 ± 303 g CO2 ‐C m −2 for the complete production cycle after accounting for C export at harvest (1, 183 g C m −2 ), and was approximately CO2 ‐C neutral (−21 g CO2 ‐C m −2  year −1 ) when annualized. The results of this study are consistent with studies of soil organic C which have shown limited changes following conversion to SRC willow. In the context of global decarbonization, the study indicates that the primary benefit of SRC willow production at the site is through displacement of fossil fuel emissions. Abstract : Bioenergy crops will play an increasingly important role in the decarbonisation of the energy sector through fossil fuel displacement with further potential to increase terrestrial carbon storage. Despite this, few empirical studies have quantified the ecosystem‐level carbon balance of energy crops. This study measured the carbon budget of a real‐world, short rotation coppice (SRC) willow plantation by combining ecosystem‐scale CO2 gas flux measurements with biomass yield data. The study showed the SRC was close to CO2 neutral over the full crop production cycle. This result implies the net carbon benefit of SRC at this location is through fossil fuel displacement.